PENGARUH METODE PENGERINGAN TERHADAP KADAR SENYAWA BIOAKTIF DAN AKTIVITAS ANTIOKSIDAN PADA HERBA SURUHAN (Peperomia pellucida L.) - Dewi Puspita Apsari; Muhammad Nanda Aprilianto; Ni Luh Desyani; Ni Putu Widayanti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Suruhan herb have been used globally as concoction for medical and therapeutic purposes, so that it is much needed to investigate their phytonutrients. The variations in drying methods can affect the levels of bioactive compounds and antioxidant activity, so an appropriate drying strategy is needed to produce simplicia that containing high bioactive compounds and antioxidant activity. Based on the considerations above, this study aimed to determine the effect of various drying methods strategies (direct sunlight, oven drying and wind drying) on the bioactive compounds and antioxidant activity of the suruhan herb. The extract of suruhan herb were subsequently analyzed for total flavonoids, total phenols, total tannins, and their antioxidant activity. The results showed that oven-dried suruhan herb produced the highest potential antioxidant activity, that was 94.67 ppm with total flavonoids 51.00 mgQE/g extract, total phenol 63.36 mgGAE/g extract, and total tannins 41.89 mgTAE/g extract. It can be concluded that the variety of drying strategy has a significant impact (p<0.05) on the bioactive content and antioxidant activity of the suruhan herb.